Eficiencia de la gestión municipal en el gasto público de la Municipalidad Distrital de Pinto Recodo periodo 2011 - 2014 - Ruiz Vásquez, Kerlinger (2016)
This research entitled “Demonstrate how it influences the efficiency of municipal management in the quality of public expenditure in the District Municipality of Pinto Recodo period 2011 - 2014" The research was descriptive - explanatory, for which a sample of 86 people was obtained both citizens and workers of the municipality of the district for the respective survey. For the data was used as an instrument self-directed survey which collected information about variables Efficiency of Municipal and Public Expenditure, where the questions were aimed at identifying the reason for the excess spending admiring Management; the weighted average of the last two years in office was used as indicator. For statistical data analysis Excel for tabulation and percentage we were used. Likewise, the independence of the variables significantly with chi-square test, read 95% reliability was observed. Furthermore, the objective of this research is to "determine why the efficiency of municipal management is not helping to reduce public spending of the District Municipality of Pinto Recodo period 2011 - 2014". The research findings through the survey and document analysis, shows how it influences the efficiency of municipal management in the quality of public expenditure in the District Municipality of Pinto Recodo period 2011 - 2014 " , this mean that the municipality It has no specific for the management of its budget outline guidelines , so it has to make a feedback of their management tools to use and good management of their income and to reduce their costs , as this would benefit both citizens better basic services and better quality of life among others.